Aldosterone and Acetylcholine Associations With Chronic Hypertension: Hubungan Aldosteron dan Asetilkolin dengan Hipertensi Kronis - Khutheir Abbas Ali; Ola Hassan AlSaady; Qussay Noori Raddam (Indonesian Journal on Health Science and Medicine, 2025)
General Background Hypertension is a major indicator of cardiovascular dysfunction and is regulated by complex hormonal and neural mechanisms. Specific Background Aldosterone and acetylcholine play critical roles in fluid balance, vascular tone, and blood pressure regulation. Knowledge Gap However, limited studies have examined the relationship between aldosterone and acetylcholine concentrations simultaneously in individuals with chronic hypertension. Aims This study aimed to evaluate serum aldosterone and acetylcholine levels and determine their correlation with blood pressure in adult males with chronic hypertension. Results The findings revealed a highly significant increase in aldosterone levels and a significant decrease in acetylcholine concentration in hypertensive patients compared to healthy controls. Aldosterone showed a positive correlation with both systolic and diastolic blood pressure, whereas acetylcholine demonstrated an inverse correlation with blood pressure. Novelty This study provides evidence of an inverse relationship between aldosterone and acetylcholine concentrations within the same hypertensive population. Implications These results contribute to a better physiological understanding of hypertension and highlight the importance of hormonal–neurotransmitter interactions in blood pressure regulation. Keywords: Aldosterone, Acetylcholine, Hypertension, Blood Pressure, Correlation Key Findings Highlights: Serum hormone levels differed significantly between patients and controls. Neurotransmitter concentration showed an inverse relationship with pressure values. Reciprocal association was observed between endocrine and neural markers.